2015
DOI: 10.1161/hypertensionaha.115.05356
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Decreases the Permselectivity of the Paracellular Pathway in Thick Ascending Limbs

Abstract: Thick ascending limbs (THALs) reabsorb 25–30% of the filtered NaCl. About 50–70% is reabsorbed via the transcellular pathway and 30–50% is reabsorbed through the Na-selective paracellular pathway. Nitric oxide (NO) inhibits transepithelial Na reabsorption, but its effects on the paracellular pathway are unknown. We hypothesized that NO decreases the selectivity of the paracellular pathway in THALs via cGMP-dependent protein kinase (PKG). To assess relative Na/Cl permeability ratios (PNa/PCl), we perfused rat T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 62 publications
2
12
0
Order By: Relevance
“…As a result of transcellular transport, there is a lumen-positive potential in thick ascending limbs that drives Na ϩ , Ca 2ϩ , and Mg 2ϩ reabsorption via the paracellular pathway, i.e., through the space between adjacent cells (265). Up to 50% of the total Na ϩ reabsorbed by thick ascending limbs traverses this route (263), which is selective for Na ϩ over Cl Ϫ with a Na ϩ -to-Cl Ϫ permeability ratio (PNa ϩ /PCl Ϫ ) of 2 (68,225,265,455). An important point to consider is that the estimation of the magnitude of flux through the paracellular route was made based on experiments using perfused tubules with symmetrical solutions.…”
Section: B Paracellular Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of transcellular transport, there is a lumen-positive potential in thick ascending limbs that drives Na ϩ , Ca 2ϩ , and Mg 2ϩ reabsorption via the paracellular pathway, i.e., through the space between adjacent cells (265). Up to 50% of the total Na ϩ reabsorbed by thick ascending limbs traverses this route (263), which is selective for Na ϩ over Cl Ϫ with a Na ϩ -to-Cl Ϫ permeability ratio (PNa ϩ /PCl Ϫ ) of 2 (68,225,265,455). An important point to consider is that the estimation of the magnitude of flux through the paracellular route was made based on experiments using perfused tubules with symmetrical solutions.…”
Section: B Paracellular Pathwaymentioning
confidence: 99%
“…The three NOS isoforms, NOS1, NOS2, and NOS3, were formerly known as neuronal NOS, inducible NOS, and endothelial NOS, respectively, based on the tissue or conditions in which they were first characterized. All three NOS isoforms are found in thick ascending limbs (208,562,714), where NO regulates net NaCl reabsorption through inhibition of both transcellular and paracellular pathways (455,456,502,506,543). Given the central role that NO plays in regulating thick ascending limb salt reabsorption, in addition to the fact that its production or actions in Dashed lines indicate that the complete signaling cascade is unknown.…”
Section: A) Production Of Nitric Oxide and Regulation Of Transcellularmentioning
confidence: 99%
“…NO reduces the activity of transporters in the luminal membrane and thereby transepithelial NaCl and NaHCO 3 reabsorption (7,9,31,33,34). We previously showed that NO decreases the P Na ϩ /P Cl Ϫ of the paracellular pathway in thick ascending limbs via cGMP (30). However, whether this is a result of a decrease in P Na ϩ , an increase in P Cl Ϫ , or a simultaneous change in both P Na ϩ and P Cl Ϫ in opposite directions, and how these changes alter net salt reabsorption, are still unknown.…”
mentioning
confidence: 99%
“…This is in line with the previously reported upregulation of the apical Cl − /HCO 3 − exchanger, pendrin, by Ang II in intercalated cells ( 10 ). Although it is commonly believed that appreciable Cl − movement occurs in a paracellular manner in the collecting duct (∼30% for rabbits ( 50 )) secondary to the electrogenic Na + reabsorption via ENaC by the principal cells, the tight junctions are only marginally more selective for Cl − versus Na + (ratio is 1.2–1.3:1) ( 51 ) indicating rather passive concomitant NaCl flux, as it similarly occurs in upstream nephron segments ( 52 ). Furthermore, blockade of ENaC with amiloride did not abolish lumen-to-bath Cl − movement in perfused collecting ducts ( 10 ).…”
Section: Discussionmentioning
confidence: 99%